Optical spectroscopy : methods and instrumentations - Tkachenko, Nikolai V.; ScienceDirect eBooks (Amsterdam ; Boston : Elsevier, 2006)
Optical Spectroscopy bridges a gap by providing a background on optics while focusing on spectroscopic methodologies, tools and instrumentations. The book introduces the most widely used steady-state and time-resolved spectroscopic techniques, makes comparisions between them, and provides the methodology for estimating the most important characteristics of the techniques such as sensitivity and time resolution. Recent developments in lasers, optics and electronics has had a significant impact on modern optical spectroscopic methods and instrumentations. Combining the newest lasers, advanced detectors and other high technology components researchers are able to assemble a spectroscopic instrument with characteristics that were hardly achievable a decade ago. This book will help readers to sourse spectroscopy tools to solve their problems by providing information on the most widely used methods while introducing readers to the principles of quantitative analysis of the application range for each methodology. In addition, background information is provided on optics, optical measurements and laser physics, which is of crucial importance for spectroscopic applications. * provides an overview of the most popular absorption/emission spectroscopy techniques * discusses application range, advantages and disadvantages are compared for different spectroscopy methods * provides introductions to the relevant topics such as optics and laser physics.
Optics and optical devices -- Lasers for spectroscopy applications -- Optical measurements -- Steady state absorption spectroscopy -- Steady state emission spectroscopy -- Flash-photolysis -- Time correlated single photon counting -- Frequency domain emission spectroscopy -- Picosecond time resolution with streak camera -- Pump-probe -- Emission spectroscopy with optical gating methods -- Ultra-fine spectrum resolution -- Polarization measurements -- Analysis of the measurements.
Includes bibliographical references (pages 301-303) and index.
Print version record.
Elsevier
Keywords: Optical spectroscopy; Optical instruments -- Methodology; SCIENCE -- Spectroscopy & Spectrum Analysis; Optical spectroscopy; Electronic books